Development and Validation of a Novel, Rapid Gradient HPLC Method for Simultaneous Estimation of Bioactive Marker Compounds in a Mixture of Convolvulus pluricaulis, Withania somnifera and Bacopa monnieri Extracts. (21st October 2019) - Choudhary, Sunayna; Kaur, Indu Pal; Malik, Jai
Abstract: The use of herbs as medicine is an ancient form of healthcare known to mankind. Standardization of herbal medicines is however a challenging task and is the major bottleneck in their acceptance as the primary therapeutic option. The aim of this study was to develop and validate a simple, rapid HPLC method for standardizing the mixture of extracts of three Medhya Rasayanas (neurotonic), Convolvulus pluricaulis, Withania somnifera and Bacopa monnieri . Simultaneous estimation of the respective bioactive markers of these plants viz., scopoletin, withaferin A, bacoside A 3, bacopaside II, jujubogenin and bacosaponin C has been reported for the first time. The method was developed using Waters Hybrid X-Bridge shield with BEH technology 2.5 μm, 4.6 × 75 mm column and validated according to ICH guidelines. The 20 minutes run time makes the method eco-friendly. The method was linear over a range of 12.5–400 ng/10 μL for scopoletin and 62.5–2, 000 ng/10 μL for withaferin A, bacoside A 3, bacopaside II, jujubogenin and bacosaponin C with detection limits of 8.0, 48.3, 30.4, 40.7, 15.6 and 18.9 ng/10 μL and quantification limits of 24.5, 146.5, 92.2, 123.4, 47.4 and 57.4 ng/10 μL, respectively. The correlation coefficient for each analyte was >0.999. The intra-day and inter-day precision was <2%. These results confirmed the precision, accuracy and robustness of the proposed method.